2017
DOI: 10.1111/jeu.12420
|View full text |Cite
|
Sign up to set email alerts
|

Systematics and Molecular Phylogeny of the Ciliate Genus Pseudokeronopsis (Ciliophora, Hypotrichia)

Abstract: A still challenging study on ciliate systematics is to clarify the taxonomic and phylogenetic confusions of the fascinating pigmented Pseudokeronopsis species because of their high interspecific similarities. We evaluated the identities and internal relationships within Pseudokeronopsis based on morphological descriptions in combination with the 18S and ITS-5.8S rDNA genetic distances, ITS2 secondary structures and phylogenetic analyses. Results showed that (1) Pseudokeronopsis pararubra, a species ever synony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Thus, there is a pyrimidine-pyrimidine mismatch in helix II of heterotricheans (Shazib et al 2016) and oligohymenophoreans (Coleman 2005;Miao et al 2008;Sun et al 2010Sun et al , 2013, as typical for eukaryotes (Coleman 2007;Schultz et al 2005). By contrast, this mismatch is not present in litostomateans and spirotricheans (Weisse et al 2008;Yi et al 2008;Li et al 2013Li et al , 2017. This indicates that the loss of the pyrimidine-pyrimidine mismatch is a molecular synapomorphy of litostomateans and spirotricheans, providing a further support for the SAL hypothesis based on extensive molecular data (Gentekaki et al 2014(Gentekaki et al , 2017.…”
Section: Putative Secondary Structure Of the Free-living Litostomateamentioning
confidence: 84%
See 2 more Smart Citations
“…Thus, there is a pyrimidine-pyrimidine mismatch in helix II of heterotricheans (Shazib et al 2016) and oligohymenophoreans (Coleman 2005;Miao et al 2008;Sun et al 2010Sun et al , 2013, as typical for eukaryotes (Coleman 2007;Schultz et al 2005). By contrast, this mismatch is not present in litostomateans and spirotricheans (Weisse et al 2008;Yi et al 2008;Li et al 2013Li et al , 2017. This indicates that the loss of the pyrimidine-pyrimidine mismatch is a molecular synapomorphy of litostomateans and spirotricheans, providing a further support for the SAL hypothesis based on extensive molecular data (Gentekaki et al 2014(Gentekaki et al , 2017.…”
Section: Putative Secondary Structure Of the Free-living Litostomateamentioning
confidence: 84%
“…Therefore, this molecule has become a popular tool in many phylogenetic studies, including those on ciliates (e.g. Coleman 2005;Miao et al 2008;Weisse et al 2008;Yi et al 2008;Sun et al 2010Sun et al , 2013Ponce-Gordo et al 2011;Li et al 2013;Shazib et al 2016;Li et al 2017).…”
Section: Putative Secondary Structure Of the Free-living Litostomateamentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analyses based on concatenation of multiple genes are increasingly used to give better interpretations evolutionary relationships within different ciliate groups (Antipa, Dolan, Lynn, Obolkina, & Strüder‐Kypke, ; Gao, Gao, Wang, Katz, & Song, ; Gao, Warren, et al., ; Gao et al., ; Gentekaki et al., ; Huang, Luo, Bourland, Gao, & Gao, ; Li, Liu, Gao, Warren, & Song, ; Li, Zhan, & Xu, ; Pan, Jiang, Fan, Al‐Farraj, & Gao, ; Sung, Sung, Hywel‐Jones, & Spatafora, ; Yan, Xu, Al‐Farraj, Al‐Rasheid, & Song, ; Yan, Fan, et al., ; Zhao, Gao, Fan, Strüder‐Kypke, & Huang, ). In this study, we broaden the taxon sampling of haptorians by adding 14 small subunit ribosomal RNA (SSU‐rRNA), 12 large subunit ribosomal RNA (LSU‐rRNA) and 12 ITS1‐5.8S‐ITS2 gene sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The cortical granule type (color, size, shape, and arrangement) is an important feature in the classification of urostylid ciliate species (Berger ; Li et al. ). In our study, we found that A. australis and A. rubrus formed a clade, but the distance between them was relatively large (1.2% of sequences were dissimilar).…”
Section: Discussionmentioning
confidence: 99%